1984
DOI: 10.1021/j150669a010
|View full text |Cite
|
Sign up to set email alerts
|

Production and unimolecular decay rate of internal energy selected molecular ions in a laser reflectron time-of-flight mass spectrometer

Abstract: Monoenergetic, internal energy selected polyatomic ions are produced in a new two-laser pump-pump experiment. Low energetic parent ions produced with the first laser are further excited with the tunable second laser to a specified internal energy after extraction from the ion source. The metastable decay of energy-selected ions is monitored in a reflectron time-of-flight mass spectrometer, and as a first example, dissociation rates have been measured for two decay channels of C6H6'. The result clearly demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In photoionization-based methods the (UV laser generated) ions are accelerated by high voltages (e.g., of a Wiley–McLaren arrangement) into a time-of-flight mass spectrometer (TOF, occasionally denoted as third chamber). It can either be a linear (schematic illustration, ref ) or a reflectron arrangement (schematic illustration, ref , for more details on Re-TOFs, e.g., refs ). The mass-selected ions are detected on, e.g., a microchannel plate detector, amplified and analyzed by an oscilloscope and specialized software.…”
Section: Introduction To Experimental Methodsmentioning
confidence: 99%
“…In photoionization-based methods the (UV laser generated) ions are accelerated by high voltages (e.g., of a Wiley–McLaren arrangement) into a time-of-flight mass spectrometer (TOF, occasionally denoted as third chamber). It can either be a linear (schematic illustration, ref ) or a reflectron arrangement (schematic illustration, ref , for more details on Re-TOFs, e.g., refs ). The mass-selected ions are detected on, e.g., a microchannel plate detector, amplified and analyzed by an oscilloscope and specialized software.…”
Section: Introduction To Experimental Methodsmentioning
confidence: 99%
“…Recently, however, we were able to show that vibrational state selected benzene cations can be produced by reso nance-enhanced two-photon ionization via selected inter mediate states [14][15][16]. The state selection was proved by energy analysis of the photoelectrons [17,18].…”
Section: Statistical Decay Of C 6 H 6 +mentioning
confidence: 99%
“…It is clear that the two-colour IR-UV approach results in a small, but appreciable, yield of low mass ions. It is important to understand the origin of these low mass ions, which are identified based upon the photo-ionisation/dissociation studies of Ku¨hlewind et al [77][78][79] and Holland et al 80 The wavelength dependence of each fragment ion identified in the inset of Fig. 3 is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%